Tolerability of High-Volume Subcutaneous Injections of a Viscous Placebo Buffer: A Randomized, Crossover Study in Healthy Subjects - Dias, Clapton; Abosaleem, Bassam; Crispino, Caroline; Gao, Bing; Shaywitz, Adam (AAPS PharmSciTech, 2015)
Monoclonal antibody biotherapeutics are often administered by subcutaneous (SC) injection. Due to dose requirements and formulation limitations, SC injections >1 mL are often required. We used a viscous placebo buffer (5 cP), characteristic of a high-concentration antibody formulation, to investigate the effect of dose volume and injection rate on the tolerability of higher-volume SC injections. In this randomized, crossover, single-center study, 48 healthy adults received one 1.2-mL bolus injection over 5 s and three 3.5-mL injections over 1, 4, and 10 min in different abdominal quadrants, with each injection separated by approximately 2 h. The primary objective was to compare pain scores associated with the injections, immediately after administration and 1 h later, using a 100-mm visual analog scale (VAS). Secondary objectives included assessment of adverse events, including injection site reactions and swelling. Mean age was 38.4 (11.6) years and 20 subjects (42%) were female. Lowest mean VAS score was for the 10-min (6.83 mm) and highest for the 1-min injection (19.13 mm). One hour after administration, mean VAS scores were <3.5 mm for all injections. Swelling was similar among the three 3.5-mL injections. After needle removal, leakage occurred following 14 (29%) 1.2-mL injections, eight (17%) 4-min injections, five (10%) 1-min injections, and four (8%) 10-min injections. Fifteen subjects (31%) experienced an adverse event, none of which was serious, fatal, or led to study discontinuation. All injection durations were well tolerated, suggesting a single large-volume SC injection of a biotherapeutic agent could be used instead of multiple injections.